Yield of a short rotation coppice plantation of Salix spp. in Buenos Aires, Argentina - Doffo, Guillermo N; Achinelli, Fabio G; Rodríguez, María E; Luquez, Virginia M (BOSQUE, 2017)
In Argentina, energy production depends mostly on fossil fuels; hence it is desirable to diversify the energy sources including renewable fuels such as forest biomass. A drawback for this development is the lack of information about the productivity of short rotation coppice systems (SRC) under local conditions. Willows are used in several countries as a source of biomass for energy, although in Argentina the information about yield at local level is scarce. An SRC system was established in agricultural soil in Buenos Aires Province, Argentina. The aim of this work was to estimate the effects of irrigation, plantation density and genotype on biomass production. The clones used were the hybrid Salix matsudana x Salix alba `Barrett 13-44 INTA´ and the open pollinated Salix alba `Yaguareté INTA - CIEF´. There were no statistically significant effects of clone and plantation density on biomass productivity. The only significant factor was irrigation, which explained 83 to 92 % of yield variability. The dry biomass yields are similar to those reported elsewhere for rainfed SRC willows, ranging between 11.1 and 22.6 Mg ha-1 year-1.